Experimental study on surface properties of the PMMA used in high power spark gaps - Ruoyu Han; Jiawei Wu; Weidong Ding; Yunfei Liu; Yang Gou (AIP Advances, 2017)
This paper studies the surface properties of the Polymethylmethacrylate (PMMA) insulator samples used in high power spark gaps. Experiments on surface morphology, surface profile, surface chemical composition and surface leakage current were performed. Metal particles ejected in tangent direction of discharge spots were researched on the sample surface. Three kinds of distinct bands were found on the surface after 1500 shots: colorless and transparent sinking band, black band, and grey powdered coating band. The thickness of the coating band was tens of microns and the maximum radial erosion rate was about 10 μm/C. Surface content analysis indicated that the powdered coating was a mixture of decomposed insulator material and electrode material oxides. In addition, leakage current significantly depended on water content in the chamber and presented an U-shape curve distribution along the insulator surface, in keeping with the amount of powdered coating due to shock waves. Possible reasons of the surface property changes were discussed. Electroconductive oxides of low valence states of Cu and W produced by the reactions between electrode materials and arc plasmas were considered to be the cause of dielectric performance degradation.